Ameliorative effect and mechanism of Si-Ni-San on chronic stress-induced diarrhea-irritable bowel syndrome in rats - Hui-Yu Chen; Hui-Yu Chen; Hui-Yu Chen; Hui-Yu Chen; Hui-Yu Chen; Hui-Yu Chen; Hui-Yu Chen; Jian Liu; Jian Liu; Jian Liu; Jian Liu; Jian Liu; et al. (Frontiers Media S.A., 2022)
Background: Chronic stress-induced diarrhea is a common clinical condition, characterized by an abnormal bowel movement and loose stools, which lacks effective treatment in the clinic. Si-Ni-San (SNS) is a compound traditional Chinese medicine extensively used in China for stress-related diarrhea. However, the mechanism is unclear.Methods: Male Wistar rats (200 ± 20 g) were placed in a restraint cylinder and fixed horizontally for 3 h once daily for 21 consecutive days to establish a chronic restraint stress (CRS) rat model. SNS (0.6944 g/kg or 1.3888 g/kg) was given by gavage 1 h before the restraint once daily for 21 consecutive days. We examined the fecal score, dopamine β hydroxylase (DβH), and c-fos expression in locus coeruleus, norepinephrine (NE) content in ileum and plasma, expression of α1 adrenergic receptors, MLCK, MLC, and p-MLC in the colon and mesenteric arteries, contraction of isolated mesenteric arteries, The expression of subunit δ of ATP synthase (ATP5D) in intestinal tissues, ATP, ADP, and AMP content in the ileum and colon, occludin expression between ileum epithelial cells, the number of enterochromaffin cells (ECs) and mast cells (MCs) in the ileum, and 5-hydroxytryptamine (5-HT) content in the ileum and plasma.Results: After SNS treatment, the fecal score was improved. The increased expression of DβH and c-fos in locus coeruleus was inhibited. SNS suppressed the increased NE content in the ileum and plasma, down-regulated α1 adrenergic receptors in mesenteric arteries and MLCK, MLC, p-MLC in the colon and mesenteric arteries, and inhibited the contraction of mesenteric arteries. SNS also increased the ATP content in the ileum and colon, inhibited low expression of ATP5D in intestinal tissues, inhibited the decrease of ATP/ADP in the ileum and ATP/AMP in the colon, and up-regulated the occludin expression between ileum epithelial cells. In addition, SNS inhibited the increase of ECs and MCs in the ileum and the increase of 5-HT content in the ileum and plasma.Conclusion: This study demonstrated that SNS could improve CRS-induced abnormal feces in rats. This effect was related to the inhibition of CRS-induced increased expression of DβH and c-fos in the locus coeruleus, NE content in the ileum and plasma, and the contraction of isolated mesenteric arteries; inhibition of energy metabolism abnormality and decreased occludin expression; inhibition of increased ECs and MCs in the ileum, and 5-HT content in the ileum and plasma.